Barriers and Benefits of Information Communication Technologies Used by Health Care Aides - Perez, Hector; Neubauer, Noelannah; Marshall, Samantha; Philip, Serrina; Miguel-Cruz, Antonio; Liu, Lili (Applied Clinical Informatics, 2022)
Background Although information and communication technologies (ICT) are becoming more common among health care providers, there is little evidence on how ICT can support health care aides. Health care aides, also known as personal care workers, are unlicensed service providers who encompass the second largest workforce, next to nurses, that provide care to older adults in Canada.Objective The purpose of this literature review is to examine the range and extent of barriers and benefits of ICT used by health care workers to manage and coordinate the care-delivery workflow for their clients.Methods We conducted a literature review to examine the range and extent of ICT used by health care aides to manage and coordinate their care delivery, workflow, and activities. We identified 8,958 studies of which 40 were included for descriptive analyses.Results We distinguished the following five different purposes for the use and implementation of ICT by health care aides: (1) improve everyday work, (2) access electronic health records for home care, (3) facilitate client assessment and care planning, (4) enhance communication, and (5) provide care remotely. We identified 128 barriers and 130 benefits related to adopting ICT. Most of the barriers referred to incomplete hardware and software features, time-consuming ICT adoption, heavy or increased workloads, perceived lack of usefulness of ICT, cost or budget restrictions, security and privacy concerns, and lack of integration with technologies. The benefits for health care aides' adoption of ICT were improvements in communication, support to workflows and processes, improvements in resource planning and health care aides' services, and improvements in access to information and documentation.Conclusion Health care aides are an essential part of the health care system. They provide one-on-one care to their clients in everyday tasks. Despite the scarce information related to health care aides, we identified many benefits of ICT adoption.
Keywords: information technology; delivery of health care; health personnel; workflow; aged